Assessment of the manganese cluster’s oxidation state via photoactivation of photosystem II microcrystals - Cheah, Mun Hon (Proc Natl Acad Sci U S A, 2020)
Knowledge of the manganese oxidation states of the oxygen-evolving Mn(4)CaO(5) cluster in photosystem II (PSII) is crucial toward understanding the mechanism of biological water oxidation. There is a 4 decade long debate on this topic that historically originates from the observation of a multiline electron paramagnetic resonance (EPR) signal with effective total spin of S = 1/2 in the singly oxidized S(2) state of this cluster. This signal implies an overall oxidation state of either Mn(III)(3)Mn(IV) or Mn(III)Mn(IV)(3) for the S(2) state. These 2 competing assignments are commonly known as “low oxidation (LO)” and “high oxidation (HO)” models of the Mn(4)CaO(5) cluster. Recent advanced EPR and Mn K-edge X-ray spectroscopy studies converge upon the HO model. However, doubts about these assignments have been voiced, fueled especially by studies counting the number of flash-driven electron removals required for the assembly of an active Mn(4)CaO(5) cluster starting from Mn(II) and Mn-free PSII. This process, known as photoactivation, appeared to support the LO model since the first oxygen is reported to evolve already after 7 flashes. In this study, we improved the quantum yield and sensitivity of the photoactivation experiment by employing PSII microcrystals that retained all protein subunits after complete manganese removal and by oxygen detection via a custom built thin-layer cell connected to a membrane inlet mass spectrometer. We demonstrate that 9 flashes by a nanosecond laser are required for the production of the first oxygen, which proves that the HO model provides the correct description of the Mn(4)CaO(5) cluster’s oxidation states.